The Influence of Entrepreneurial Orientation, Market Orientation, and Business Network on Competitive Advantage in Msmes in Rengel Tuban - Khikma Anggita; Nurul Badriyah; Evi Fitrotun (Jurnal Price : Ekonomi dan Akuntasi, 2024)
This study aims to analyze the influence of entrepreneurial orientation, market orientation, and business network on competitive advantage in micro, small, and medium enterprises (MSMEs) in Rengel District, Tuban Regency. The research uses a quantitative approach with a survey method. The research population is 1,427 MSME actors in Rengel District, while the sample was determined using the Slovin formula so that 93 respondents were obtained. Primary data was collected through a Likert scale questionnaire and analyzed using IBM SPSS 25. Data analysis techniques include validity test, reliability test, classical assumption test, multiple linear regression, t test, F test, and determination coefficient. The results showed that entrepreneurial orientation did not have a significant effect on competitive advantage (t = 0.931; sig. = 0.355). Market orientation has a positive and significant effect on competitive advantage (t = 6.128; sig. = 0.000), while business network also has a positive and significant effect on competitive advantage (t = 4.910; sig. = 0.000). Simultaneously, entrepreneurial orientation, market orientation, and business network had a significant effect on competitive advantage (F = 28,496; sig. = 0.000). The Adjusted R Square value of 0.473 indicates that the three independent variables are able to explain 47.3% of the variation in competitive advantage. This finding confirms that market orientation and business network are important factors in increasing the competitiveness of MSMEs in Rengel Tuban.